PERHITUNGAN, PENYETORAN, PELAPORAN, DAN PENCATATAN AKUNTANSI PAJAK PERTAMBAHAN NILAI MASA MARET 2025 PADA PT. NCL INTER LOGISTIK INDONESIA - Hidayat, Achmad; Enggun Gunawan; Ahmad Dihyan Firza (POLITEKNIK LP3I JAKARTA, 2025)
Calculation, payment, reporting, and recording of Value Added Tax (VAT) at PT. NCL Inter Logistik Indonesia. VAT is an indirect tax on the consumption of Taxable Goods and/or Taxable Services within the customs area, as regulated in Law Number 8 of 1983, most recently amended by Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP). The method used was descriptive qualitative, with data collection techniques consisting of observation, interviews, and documentation studies conducted during the March 2025 tax period. The results indicate that the company has fulfilled its tax obligations in accordance with applicable regulations. This process includes issuing tax invoices with the appropriate object code, calculating VAT based on the replacement value or effective rate, payment through the Billing System menu integrated with e-Billing, reporting Periodic Tax Returns through the Coretax website, and maintaining accounting records in accordance with standards. This implementation reflects compliance with the self-assessment system adopted in the Indonesian tax system and complies with the provisions of Regulation (PER)-14/PJ/2022 and Regulation (PMK) No. 58/PMK.03/2022. Thus, the company has implemented tax administration in an orderly and accountable manner.